Dry Socket: Incidence, Clinical Features, and Predisposing Factors. (2nd June 2014) - Akinbami, Babatunde O.; Godspower, Thikan
Abstract : Background . Dry socket is a global phenomenon. The purpose of the study was to investigate the incidence of dry socket in recent times in a Nigerian Tertiary Hospital. Methods . Patients who were referred for dental extractions were included in the study. The case files of patients were obtained and information retrieved included biodata, indication for extraction, number and type of teeth extracted, oral hygiene status, compliance to oral hygiene instructions, and development of dry socket. Results . One thousand, one hundred and eighty two patients with total of 1362 teeth extracted during the 4-year period of the study were analyzed, out of which 1.4% teeth developed dry socket. The mean age (SD) was 35.2 (16.0) years. Most of the patients who presented with dry socket were in the fourth decade of life. Mandibular teeth were affected more than maxillary teeth. Molars were more affected. Retained roots and third molars were conspicuous in the cases with dry socket. Conclusion . The incidence of dry socket in our centre was lower than previous reports. Oral hygiene status, lower teeth, and female gender were significantly associated with development of dry socket. Treatment with normal saline irrigation and ZnO eugenol dressings allowed relief of the symptoms.